Development of a contact-based printing system on a controllable flatbed surface - Muhammad Nizar Jasmani (2019)
Paper has been one of the most useful materials known to man. Many believed so because paper holds a lot of creative potentials for man to exploit. One of these potentials is paper-based sensors. These sensors offer a wide range of detection method which enables them to be highly flexible. Colorimetric sensing and electrochemical sensing are some of the methods. This project discussed the potential of fabricating paper-based sensors by contact-based printing as well as designing a printer head that is suitable for this purpose. The printer head will be integrated into a 2D directional plotter to produce a system that allows the user to print a sensor of his or her design and needs. This contact-based printing system should eradicate or minimize the problems of popular printing methods such as inkjet. On top of this, contact-based printing also should also be capable of printing ink with biological molecules without rupturing them. A series of prototypes were designed to test the feasibility of this concept. These prototypes were designed using CAD software: Autodesk Fusion 360 and were fabricated by using a 3D printer. After many prototype designs, knowledge gained and research, a final design of the printer head was created and assembled. Multiple experiments, tests, and modification were conducted to ensure the efficiency and efficacy of the valve system of the printer. In addition to this, the print head print resolution was tested for multiple prints set up. All in all. Though improvements are still required for the system and the design, this project proves that the system of contact-based printing is feasible.